Literatur Review: Implementasi PjBL terhadap Kreativitas dan Berpikir Tingkat Tinggi Siswa - Islawati, Islawati; Samsuddin, Yati Bt (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out and describe the implementation of the Project-Based Learning (PjBL) project-based learning model in increasing student creativity at various levels of education. The research method used is Systematic Literature Review (SLR), which is carried out through systematic steps to identify, evaluate, and synthesize relevant articles. Articles are obtained through searches on the Sinta portal, with criteria that only include articles that are accredited and published in the last five years. The search strategy involves the use of specific keywords such as